The Semaphorin 3A inhibitor SM-345431 preserves corneal nerve and epithelial integrity in a murine dry eye model. Issue 1 (December 2017) - Yamazaki, Risa; Yamazoe, Katsuya; Yoshida, Satoru; Hatou, Shin; Inagaki, Emi; Okano, Hideyuki; Tsubota, Kazuo; Shimmura, Shigeto
Abstract Dry eye disease (DED) is a common disorder causing discomfort and ocular fatigue. Corneal nerves are compromised in DED, which may further cause loss of corneal sensation and decreased tear secretion. Semaphorin 3A (Sema3A) is expressed by the corneal epithelium under stress, and is known as an inhibitor of axonal regeneration. Using a murine dry eye model, we found that topical SM-345431, a selective Sema3A inhibitor, preserved corneal sensitivity (2.3 ± 0.3 mm versus 1.4 ± 0.1 mm in vehicle control, p = 0.004) and tear volume (1.1 ± 0.1 mm versus 0.3 ± 0.1 mm in vehicle control, p < 0.001). Fluorescein staining area of the cornea due to damage to barrier function was also reduced (4.1 ± 0.9% in SM-345431 group versus 12.9 ± 2.2% in vehicle control, p < 0.001). The incidence of corneal epithelial erosions was significantly suppressed by SM-345431 (none in SM-345431 group versus six (21%) in vehicle control, p = 0.01). Furthermore, sub-epithelial corneal nerve density and intraepithelial expression of transient receptor potential vanilloid receptor 1 (TRPV1) were significantly preserved with SM-345431. Our results suggest that inhibition of Sema3A may be an effective therapy for DED.